Exploring the Possible: Philosophical Reflection, Historical Imagination, and Narrative Agency (Invited) - Meretoja, Hanna (Narrative Works, 2016)
This article suggests that narrative studies would benefit from (hermeneutically informed) philosophical reflection on the basic assumptions underlying different conceptions of narrative, a sense of history in conceptualizing narrative and experience, and nuanced reflection on the significance of narrative for agency and our sense of the possible. It argues for conceptualizing narrative as an interpretative, dialogical, and performative activity of cultural sense-making that is integral to how we understand our past, present, and future possibilities. It proposes three ways in which acknowledging the historicity of experience allows us to explore how narratives shape historical imagination. Arguing for approaching literary narratives as explorations of human possibilities, the article ends by showing, through an analysis of Michel Houellebecq’s Submission (2015), how narrative fiction can contribute to our sense of the possible and to our understanding of narrative agency.